A solvent-free approach to extract the lipid fraction from sewer grease for biodiesel production. (August 2016) - Tu, Qingshi; Wang, Jingjing; Lu, Mingming; Brougham, Andrew; Lu, Ting
Highlights: A solvent-free approach to extract lipid fraction from sewer grease for biodiesel production. An oil extraction method without prior moisture removal. Innovation use of waste cooking oil to replace chemical solvents. Abstract: Fats, oils and greases (FOG) are the number one cause of sewer pipe blockage and have been mostly disposed of as a waste until recently. This study investigated a low cost and environmentally friendly approach to extract the lipid fraction (fatty acids and glycerides for biodiesel production) from sewer grease (SG), i.e., FOGs obtained from wastewater treatment plants (WWTPs). The lipid fraction of the sewer grease was primarily in the form of free fatty acid (FFA), at 20.7 wt%. An innovative solvent-free extraction approach was developed using waste cooking oil (WCO) to overcome the challenges of emulsion, impurities and high moisture content of the sewer grease. A 95% extraction yield of sewer grease was achieved under the optimum operating condition of 3.2:1 WCO-SG ratio (wt/wt), 70 °C and 240 min. In addition, the reusability of the WCO was also investigated. WCO can be used two to three times for sewer grease extraction with more than 90% extraction efficiency.